Histomorphological spectrum of gallbladder lesions- A prospective study from a teaching hospital (Journal of Pathology of Nepal, 2023)
Background: Prevalence of gallbladder diseases vary with socio-demographic factors and in India it is around 2-29%. Cholelithiasis causes varied histopathological changes in gallbladder mucosa like acute and chronic inflammation, cholesterolosis, hyperplasia, metaplasia, dysplasia and carcinoma. Gallbladder carcinomas often present as an incidental finding in cholecystectomy specimens. Present study was conducted to identify spectrum of histopathological lesions and to find the incidence of gallbladder carcinoma in cholecystectomy specimens received at tertiary care centre in North Indian state of Uttarakhand.Materials and Methods: A prospective study was conducted in the Department of Pathology, Government Medical College, Haldwani from January 2021 to September 2022. Total 760 cholecystectomy specimens were received during the study duration. Grossing of gallbladder specimens was done as per Gallbladder Carcinoma (GBC) expert consensus statements.Results: Out of 760 cholecystectomy specimens, 595 cases (78.29%) were obtained from females, with a female to male ratio of 3.6:1. Maximum cases were seen in 4th and 5th decades of life.  Chronic cholecystitis was the most common histopathological diagnosis [709 cases (93.28%)], followed by acute cholecystitis in 20 (2.63%), follicular cholecystitis in 14 (1.84%) cases, 02 (0.26%) each of xanthogranulomatous cholecystitis and porcelain gallbladder, 05 cases (0.66%) of high-grade dysplasia and 08 cases (1.05%) of gallbladder adenocarcinoma. Out of 08 cases of gallbladder carcinoma, six were incidental diagnoses.Conclusions: Histopathological evaluation of all resected cholecystectomy specimens is imperative for the detection of premalignant and malignant lesions that might escape in gross and radiological examination and thus could adversely affect patient outcome.